Trade-off in Capital Structure Decision in Emerging economies - Bui Thanh Khoa; Duy Tung Thai (International Journal of Psychosocial Rehabilitation, 2020)
Accompanied by the rise of Real Estate transactions is the establishment, development, and competition among real estate businesses. The study aims to test the existence of trade-off theory in capital structure among real estate companies in the emerging economies stock market, case of Vietnam. Instead of considering constant optimal leverage to test the trade-off model, we take advantage of the dynamic capital structure determined by growth opportunities, profitability, tax incentives, tangibility, liquidity, and firm size. This approach requires a dynamic panel data regression, which is estimated by system Generalized Method of Moment (Sys- GMM). Our empirical evidence shows that real estate companies listed in the Vietnamese stock market may change their leverage toward a target capital structure, which is determined by influential factors in a long-term perspective. In particular, the debt-to-asset ratio will change by approximately 14 percent, positively, in response to the difference between the current debt-to-asset ratio and the dynamic target debt-to-asset ratio.